Creative Thinking Strategies for Life: A Course for Professional Adults Using Art. (16th July 2018) - Hoffmann, Jessica D.; Ivcevic, Zorana; Maliakkal, Nadine
Abstract: To thrive in today's economy and the workforce of the future, individuals need creativity and problem‐solving skills. Emotion skills have been increasingly discussed as well, with companies listing emotional intelligence as one of the top skills needed for professional success. The present paper describes a course designed to teach professional adults two sets of creativity skills (problem finding and idea generation) and two sets of emotional intelligence skills (using emotions to facilitate thinking and understanding emotions) using visual art as a medium. The course consisted of eight, 60‐min sessions in which professional adults participated in art observation and art engagement activities. Fifty‐six professional adults completed measures of creative abilities and emotional intelligence skills in a pretest, posttest, and 2‐month follow‐up design. Participants who engaged in the course showed significant gains in the originality of their ideas on divergent thinking and problem construction tasks, as well as their self‐reported creative behavior compared with controls. No significant changes in emotion understanding were detected. We discuss the course's distinct value to creativity and emotion skills training research.